(untitled) (Biological Sciences - PJSIR, 2002)
A greenhouse experiment was conducted at University Putra Malaysia to evaluate the effects of magnesium (Mg) fertili zation on rice yield , Mg and potassium (K) uptake by rice at variable applied potassium levels . Two soils (Guar and Hutan series), three Mg rates (0, 10 and 20 kg Mg ha- 1 and three K rates (0, 20 and 40 kg 1(,0 ha- 1 were used in the study. Grain ) ) and straw yields, total Mg and total K uptakes were significantly higher in Guar series compared to Hutan series. Potas sium effect was not significant on any of the parameters. Magnesium fertilization increased grain and straw yields, Mg and K uptakes significantly in both the soils. Regression analysis indicated that estimated grain and straw yield responses to added Mg were linear in nature in Guar series while these were quadratic in nature in Hutan series. Similar trends were found for total Mg and K uptakes. The findings of this study indicate that Mg fertilization should be done in Mg deficient soils to increase rice yield.